Decarbonizing Short-Sea Shipping: A Comparative Analysis of Diesel-Mechanical, Diesel-Electric, and Hybrid Propulsion Systems - Joessianto Eko Poetro; Urip Mudjiono; Catur Rakhmad Handoko; Hendro Agus Widodo (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
The role of short sea shipping in regional logistics operations is very important. With pressures from IMO regulations (EEXI and CII) growing, the maritime industry must adopt more efficient propulsion. The impact of marine technology choice on the shipping industry and its effect on the entire economy is often overlooked by society. In this paper, a techno-economic and environmental comparison of three propulsion architectures for a 5000 GT Ro-Ro passenger ferry is presented. These architectures include conventional diesel-mechanical (DM), diesel-electric (DE), and parallel hybrid (PH). The project developed a simulation framework leveraging operational profiles that were obtained from Automatic Identification System (AIS) data through the national AIS archive Marine Cadastre. The fuel consumption, emissions (CO₂, NOₓ, and SOₓ), and life-cycle cost (LCC) of all three systems were evaluated over a 20-year planning horizon. The findings demonstrate that PH approach is responsible for a 25.0% decline in yearly fuel consumption and CO₂ emission as compared to DM baseline and 14.3% compared to DE system. While the PH system necessitates 31% more CAPEX than the DM system, its payback period is approximately 2.15 years because of significant savings on operating cost. This framework, combining quantitative evidence and systematic decision-making processes, will help ship owners and other policy makers choose the best propulsion technologies to decarbonise short-sea shipping fleets.